SLIDING MODE CONTROL FOR PARALLEL ROBOTS DRIVEN BY ELECTRIC MOTORS IN TASK SPACE - Hoang, Nguyen Quang; Vuong, Vu Duc (Journal of Computer Science and Cybernetics, 2018)
This paper addresses the modelling of parallel robots including electric actuators. The dynamic model of the system is derived by applying the substructure method and Lagrangian equations with multipliers in form of redundant generalized coordinates. These equations are then transformed to the form of minimal coordinates of operational variables. Based on this form a sliding mode controller is designed for trajectory tracking in task space. Numerical simulations in MATLAB are carried out based on the 3RRR parallel robot in order to show the effectiveness of the proposal approach. The obtained results show a good behavior of the proposed task space tracking controller.